Innovation practices and performance of manufacturing SMEs in Kedah - Azrul, Abdullah (2017)
The purpose of this research is to assess the innovation practices and performance in small and medium-sized enterprises (SMEs) from the resource-based view (RBV) perspective in the Malaysian manufacturing sector. The research focused on SMEs because of the importance of SMEs in the economy and the high percentage of them in the Malaysian business population. Furthermore, manufacturing SMEs are mostly involved in innovation activities. The present research assessed the relationship between innovation practices, namely innovation strategy, organizational formal structure, innovation culture, customer and supplier relationship; and technological capabilities on SME performance. This research used survey methodology by questionnaire, then analysed by descriptive analysis, correlation and regression analysis. Findings showed that dimension of innovation strategy and technological capabilities has a positive significant relationship and influence on SME performance. This study has contributed to the flow of RBV and innovation research and provided important contributions for practitioners in developing policies and strategies for promoting innovation among SMEs in Malaysia